PENGARUH LDR, CAR, ROA DAN NPL TERHADAP PENYALURAN KREDIT PADA BANK UMUM DI INDONESIA PERIODE 2008 – 2013 - Amalia Yuliana (Jurnal Dinamika Manajemen, 2014)
Research purpose is to analyze the influence of Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Return on Asset (ROA), Non Performing Loan (NPL) and its implication to credit distribution at commercial banks in Indonesian in the period of 2008-2013 year. This research used path analysis method with substructure model. The result of substructure I indicate that Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), and Non Performing Loan (NPL) have significantly effect to Return On Asset (ROA). The result of substructure II indicates that Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Return on Asset (ROA) and Non Performing Loan (NPL) have significantly effect to credit distribution. Key Words : Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Return On Asset (ROA), Non Performing Loan (NPL) and Credit Distribution.